Successful Applications Analysis System at PT. Carefastindo Sumbagut Region Using Structural Equation Model - Melia Riska; Edy Rahman Syahputra; Ahmad Zakir (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2021)
To increase productivity and help achieve quality, time standards, and satisfaction for both consumers and employees within the company can be assisted by applying information technology. The implementation of Enterprise Resort Planning at PT Carefastindo Sumbagut Region needs to be measured for the quality of its use so that the level of success of its implementation is known. The research was conducted by taking samples of employees of PT Carefastindo Sumbagut Region who are ERP users. To measure the success rate of ERP implementation at PT Carefastindo, the main instrument of data collection is a questionnaire and is measured by a Likert scale. The number of respondents in this study were 95 respondents. The data analysis method used is the Structural Equation Model (SEM) with the DeLone and McLean information system success model approach. The results of this study indicate that the ERP implementation model at PT Carefastindo Sumbagut Region is influenced by three variables, namely: system quality, information quality and net benefit.